Detecting motion changes with peripheral vision: On the superiority of fixating over smooth-pursuit tracking. (June 2020) - Vater, Christian; Klostermann, André; Kredel, Ralf; Hossner, Ernst-Joachim
Highlights: Impaired change detection during smooth-pursuit eye movements at large eccentricities. Response times increase with eccentricity for SPEM but not for fixations. Retinal image motion might explain impaired performance during pursuit. Abstract: Detecting motion changes is a fundamental prerequisite for solving tasks in sports and in everyday life. It is known that peripheral vision is used to detect these changes and that saccades impair detection performance. However, comparatively little is known about the role of smooth-pursuit eye-movements (SPEMs) during these tasks. Therefore, we compared peripheral motion-change detection during SPEM and fixation at eccentricities up to 18°, simulating the perceptual demands of real-life situations. Based on expert gaze behavior in sports, we predicted that motion detection should be better during fixation than SPEM. In a series of three experiments, we consistently found that detection rates and response times were impaired during SPEM compared to fixation, particularly at 18° eccentricity. With an invisible pursuit object and targets moving ahead rather than behind the pursued object, performance differences in response times declined, whereas differences in detection rates interestingly remained unmoved. We argue that retinal image motion and attentional demands are reasons for SPEM impairments.